БЕЗДАВАЧЕВЕ КЕРУВАННЯ ДВИГУНОМ ПОСТІЙНОГО СТРУМУ - Пересада, С.М.; Ніконенко, Є.О.; Пижов, В.М.; Родькін, Д.І. (Інститут електродинаміки Національної академії наук України, 2021)
In this paper, a new speed control algorithm for a permanent magnet DC motor which does not require implementation of the angular speed sensor is presented. Three steps are performed to develop the control system: design of speed tracking control algorithm assuming the speed measurement; design of speed observer; design of sensorless speed control algorithm based on the principle of separation. Information about speed is taken from the speed observer using the motor current value. The stability of the composite system dynamics consisting of three subsystems (the speed regulation loop, current regulation loop, and speed observer) is analyzed. The feedback gains tuning procedure for decoupling of three subsystems is given. The simulation results show that the dynamic performance of the designed system is similar to the performance of the system with angular speed measurement. The resulting closed-loop system has structural robustness properties with respect to parametric and coordinate disturbances. References 12, figures 2.